Growth Hormone (GH) Treatment Decreases Plasma Kisspeptin Levels in GH-Deficient Adults with Prader–Willi Syndrome - Giménez-Palop, Olga (J Clin Med, 2021)
Obesity and growth hormone (GH)-deficiency are consistent features of Prader–Willi syndrome (PWS). Centrally, kisspeptin is involved in regulating reproductive function and can stimulate hypothalamic hormones such as GH. Peripherally, kisspeptin signaling influences energy and metabolic status. We evaluated the effect of 12-month GH treatment on plasma kisspeptin levels in 27 GH-deficient adult PWS patients and analyzed its relationship with metabolic and anthropometric changes. Twenty-seven matched obese subjects and 22 healthy subjects were also studied. Before treatment, plasma kisspeptin concentrations in PWS and obese subjects were similar (140.20 (23.5–156.8) pg/mL vs. 141.96 (113.9–165.6) pg/mL, respectively, p = 0.979)) and higher (p = 0.019) than in healthy subjects (124.58 (107.3–139.0) pg/mL); plasma leptin concentrations were similar in PWS and obese subjects (48.15 (28.80–67.10) ng/mL vs. 33.10 (20.50–67.30) ng/mL, respectively, p = 0.152) and higher (p < 0.001) than in healthy subjects (14.80 (11.37–67.30) ng/mL). After GH therapy, lean body mass increased 2.1% (p = 0.03), total fat mass decreased 1.6% (p = 0.005), and plasma kisspeptin decreased to levels observed in normal-weight subjects (125.1(106.2–153.4) pg/mL, p = 0.027). BMI and leptin levels remained unchanged. In conclusion, 12-month GH therapy improved body composition and decreased plasma kisspeptin in GH deficient adults with PWS. All data are expressed in median (interquartile range).